2014
DOI: 10.1111/plb.12255
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of the leaf rolling mutant sll2 reveals complex nature in regulation of bulliform cell development in rice (Oryza sativa L.)

Abstract: Bulliform cells are large, thin-walled and highly vacuolated cells, and play an important role in controlling leaf rolling in response to drought and high temperature. However, the molecular mechanisms regulating bulliform cell development have not been well documented. Here, we report isolation and characterisation of a rice leaf-rolling mutant, named shallot-like 2 (sll2). The sll2 plants exhibit adaxially rolled leaves, starting from the sixth leaf stage, accompanied by increased photosynthesis and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 52 publications
(20 reference statements)
0
40
0
3
Order By: Relevance
“…Several genetic regulators of leaf rolling have been identified in rice, and some of the recently identified ones include ROLLED LEAF9/SHALLOT-LIKE1 (Zhang et al, 2009), SHALLOT-LIKE2 (Zhang et al, 2015), ROLLED AND ERECT LEAF1 (Chen et al, 2015), ROLLED AND ERECT LEAF2 (Yang et al, 2016), SEMI-ROLLED LEAF1 (Xiang et al, 2012), SEMI-ROLLED LEAF2 (Liu et al, 2016), ROLLING LEAF14 (Fang et al, 2012), and LAT-ERAL ORGAN BOUNDARIES DOMAIN GENE (Li et al, 2016b). Mutants of these genes show either adaxially (inward) or abaxially (outward) rolled-leaf phenotypes, which is usually associated with altered development of bulliform cells.…”
mentioning
confidence: 99%
“…Several genetic regulators of leaf rolling have been identified in rice, and some of the recently identified ones include ROLLED LEAF9/SHALLOT-LIKE1 (Zhang et al, 2009), SHALLOT-LIKE2 (Zhang et al, 2015), ROLLED AND ERECT LEAF1 (Chen et al, 2015), ROLLED AND ERECT LEAF2 (Yang et al, 2016), SEMI-ROLLED LEAF1 (Xiang et al, 2012), SEMI-ROLLED LEAF2 (Liu et al, 2016), ROLLING LEAF14 (Fang et al, 2012), and LAT-ERAL ORGAN BOUNDARIES DOMAIN GENE (Li et al, 2016b). Mutants of these genes show either adaxially (inward) or abaxially (outward) rolled-leaf phenotypes, which is usually associated with altered development of bulliform cells.…”
mentioning
confidence: 99%
“…Bulliform cells are located between the vascular veins of the leaf in rice. Previous studies have demonstrated that changes in the number and area of the bulliform cells result in leaf rolling ( Zhang et al, 2009 , 2015 ; Li et al, 2010 ). Therefore, we performed transverse sectioning so that we could examine the leaves of OE- OsRRK1 and WT plants.…”
Section: Resultsmentioning
confidence: 99%
“…In rice, two types of leaf rolling (adaxial rolling and abaxial rolling) have been related to the abnormal development of bulliform cells. Changes in the number, volume, and localization of bulliform cells can result in lack of osmotic pressure to support the normal form of the blade, and then, the leaf becomes rolled ( Zhang et al, 2015 ). Generally, a leaf displays adaxial rolling when the number and size of bulliform cells are decreased in rice.…”
Section: Introductionmentioning
confidence: 99%
“…The shallot-like 2 rolling leaf mutant (sll2) exhibits adaxially rolled leaves accompanied by increased photosynthesis and reduced plant height and tiller number. The shrinkage of bulliform cells is considered responsible for the formation of inward-curved leaves [24]. NRL2, also known as SRL2 and AVB, encodes a novel protein with unknown biochemical function [25].…”
Section: Introductionmentioning
confidence: 99%